No time for that? An investigation of mindfulness and stress in first-year engineering design. (23rd February 2022) - Nolte, Hannah; Huff, Jacquelyn; McComb, Christopher
Abstract: Engineering design induces mental stress for students and the sources of stress for each stage of design are unique. Therefore, strategies are needed to manage the stress of engineering design that are applicable across the design process. This study investigated the effect of a brief mindfulness-based intervention on first-year students' cognitive stress during concept generation, concept selection and physical modelling. It was found that the mindfulness-based intervention did increase one aspect of students' state mindfulness (though the effect was small). While prior work indicates that increased mindfulness can lower perceived stress, the increase in students' state mindfulness during this study was not found to have an observable impact on students' stress experience. However, students were receptive to completing a mindfulness-based activity in-class and perceived multiple benefits. Physical modelling was the most stressful of the design tasks while concept generation and concept selection produced similar levels of stress. Students used five reoccurring mechanisms for coping with the stress of design including focusing on the task, minimising the importance of their performance, breathing, taking a break and avoidance/distraction. More research should be conducted with longer duration mindfulness-based interventions to understand their potential as a stress management strategy for engineering design.